WORKLOAD RELATION BASED ON WORKLOAD ASSESSMENT WITH THE COMPLETENESS OF NURSING CARE DOCUMENTATION BY IMPLEMENTING NURSES IN THE EMERGENCY DEPARTMENT OF RSU. ANUTAPURA PALU AND RSU. UNDATA PALU - Sasnita Salam; Titin Andri Wihastuti; Tony Suharsono (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Proper, readable, and complete documentation will have an impact on the quality of care and defense of potential malpractice suits, may be used as legal evidence in the event of a claim, but much of the nursing documentation is found to be incompatible or does not contain the necessary information in the case of the judiciary, lack of records or documentation in the patient’s medical record often hampers the exercise of the protection of nursing professional rights, both legally and administratively. The purpose of this research is to know the relation of workload factor based on workload assessment with the completeness of nursing care documentation by the nurses in the room IGD RSU. Anutapura Palu and RSU. Undata Palu. This research use correlation analytic design with cross sectional approach with total sampling to 65 samples period from 25 March 2017 until 25 April 2017. in IGD RSU room. Anutapura Palu and RSU. Undata Palu. From result of bivariate analysis known that there is correlation between work load factor with completeness of nursing care documentation with p value = 0,022. The result of regression test showed that the work load factor has regression coefficient value is -15.648 (negative value), which means that the higher workload, the percentage of completeness of the documentation of nursing care will be lower.